Long acting muscarinic antagonists for the treatment of chronic obstructive pulmonary disease: a review of current and developing drugs. (1st February 2017) - Mastrodicasa, Mark A.; Droege, Christopher A.; Mulhall, Aaron M.; Ernst, Neil E.; Panos, Ralph J.; Zafar, Muhammad A.
ABSTRACT: Introduction: Long acting muscarinic receptor antagonists (LAMA) reverse airflow obstruction by antagonizing para-sympathetic bronchoconstricting effects within the airways. For years, tiotropium, has been the cornerstone LAMA for chronic obstructive pulmonary disease (COPD) management. Recently, new agents, aclidinium bromide, glycopyrronium bromide, and umeclidinium bromide, have been developed and introduced into clinical practice. Areas covered: This article reviews the clinical efficacy and adverse effects of currently available LAMAs in COPD treatment as well as developing LAMAs in early clinical trials and preclinical studies (V0162, TD-4208, CHF 5407, AZD9164, AZD8683, bencycloquidium). In addition, a new class of molecule that combines muscarinic antagonist and β2-adrenergic properties (MABA) is described and current developmental progress discussed (GSK-961081, THRX-200495). Expert opinion: Future key areas for developing drugs for the management of COPD include prolonged duration of action, optimal delivery systems, synergistic combinations with other drugs, maximization of benefits and minimization of adverse effects. The development of new LAMA and MABA molecules provides exciting progress towards simpler and more effective COPD management.